Análisis de factibilidad de la implementación de un Sistema Contable para la gestión de los ingresos y egresos en la Empresa Reparaciones Agricolas Fernandez ubicada en la ciudad de Babahoyo - Bajaña Contreras, Kevin Anthony (2021)
This research is carried out in the company "Reparaciones Agrícolas Fernández" located in the city of Babahoyo. The main work of this entity is to repair and sell parts of all types of agricultural machinery, this entity has been working in the market for 30 years, currently it consists of 7 workers including the owner Mr. José Luis Fernández Macías, the biggest problem that this company has is that it has physically kept its sales and purchases record all these years, it has not had the opportunity to keep its records digitally (system), thus having not very good results for the entity such as loss of information, mismanagement of its records and other things. That is why a feasibility analysis will be carried out to carry out the implementation of an accounting system for the management of the company's income and expenses that will allow it to improve the efficiency and effectiveness of its accounting functions and thus facilitate better control. of the administration. With the research carried out we will have accurate information and with the feasibility study we will find out if it is feasible and feasible to implement the system.